The Effectiveness of Using the Quizizz Application in Conducting Learning Outcomes Evaluations on Thaharah Material at UPTD SD Negeri 47 Parepare - Desy Pratiwi; Firman; Muh. Dahlan; Usman; Marhani (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
This research aims to determine the use of the Quizizz application in learning Islamic Religious Education and Character at UPTD SD Negeri 47 Parepare. Then, to find out the implementation of the evaluation of Islamic Religious Education and Character Education learning outcomes at UPTD SD Negeri 47 Parepare using the Quizizz application. And to find out the effectiveness of using the Quizizz application in carrying out evaluation of learning outcomes on thaharah material at UPTD SD Negeri 47 Parepare. This research is a type of experimental research. Experimental research is research carried out to find the consequences of something done intentionally by the researcher. The use of the Quizizz application in learning Islamic Religious Education and Character Class IV UPTD SD Negeri 47 Parepare is in the very good category, namely 84.6% of the ideal score. These results were obtained by analyzing the results of a questionnaire that was distributed to 22 respondents. This shows that learning using media in the form of applications in the learning and evaluation process can have a good impact on the learning process so that it is more varied and interesting. The implementation of the evaluation of Islamic Religious Education and Character Education learning outcomes using the Quizizz application has been carried out according to the specified steps. This can be seen from the results of observing student activities which are in the very good category, namely 89% and teacher activities which are in the very good category, namely 97.5%. The effectiveness of using the Quizizz application in evaluating the learning outcomes of thaharah material in class IV UPTD SD Negeri 47 Parepare can be viewed from two aspects, namely in terms of student responses via questionnaires and in terms of student learning outcomes. Student responses via a questionnaire regarding the effectiveness of using the Quizizz application in evaluating learning outcomes for thaharah material were in the very good category, namely 84.3%. Meanwhile, student learning results showed an increase from the average pretest score of 63.41 to 90.59 in the posttest score. The increase in score obtained can also be seen from the Mean N-gain score, namely 0.7704, from a g value ? 0.7, so that in the gain index category, it is included in the high criteria. Therefore, based on data from the N-gain score, it can be concluded that the use of the Quizizz application is effective in carrying out evaluation of learning outcomes on thaharah material in class IV UPTD SD Negeri 47 Parepare.